Everything that's interesting is ...new : The Dakis Joannou Collection. - Deitch, Jeffrey; Joannou, Dakis; Koons, Jeff; Morgan, Stuart; Athens School of Fine Arts, "the factory", Athens; Museum of Modern Art, Kobehavn; Guggenheim Museum, New York (Athene : Deste Foundation for Contemporary Art, 1996)
Abramovic, Marina ; Acconci, Vito ; Adams, Dennis ; Anderson, Laurie ; Antoni, Janine ; Arman ; Armleder, John M. ; Artschwager, Richard ; Baldessari, John ; Barney, Matthew ; Beecroft, Vanessa ; Bickerton, Ashley ; Bleckner, Ross ; Boetti, Alighiero ; Borofsky, Jonathan ; Chapman, Dinos & Jake ; Clegg & Guttmann ; Crash ; Crewdson, Gregory ; Davey, Grenville ; Delvoye, Wim ; de Maria, Walter ; Dogg, John ; Donegan, Cheryl ; Douglas, Stan ; Duchamp, Marcel ; Fischer, R.M. ; Fischli & Weiss ; Riverhead (New York) ; Förg, Gunther ; Fritsch, Katharina ; Gilbert & George ; Gober, Robert ; Goldstein, Jack ; Graham, Dan ; Halley, Peter ; Hirst, Damien ; Holzer, Jenny ; Horn, Rebecca ; Judd, Donald ; Kelley, Mike ; Kemps, Niek ; Kessler, Jon ; Khedoori, Toba ; Kippenberger, Martin ; Koons, Jeff ; Kosuth, Joseph ; Kounellis, Jannis ; Kruger, Barbara ; Lappas, George ; Larner, Liz ; Lemieux, Annette ; Levine, Sherrie ; Linke, Simon ; Man Ray ; Manzoni, Piero ; Martori, Patty ; Marclay, Christian ; McCarthy, Paul ; McCollum, Allan ; Merz, Gerhard ; Miyajima, Tatsuo ; Morimura, Yasumasa ; Mullican, Matt ; Muñoz, Juan ; Nagy, Peter ; Nauman, Bruce ; Noland, Cady ; Orozco, Gabriel ; Pascali, Pino ; Picabia, Francis ; Prince, Richard ; Ray, Charles ; Robbins, David ; Rosenquist, James ; Ruscha, Ed ; Salle, David ; Scholte, Rob ; Schütte, Thomas ; Sherman, Cindy ; Simmons, Laurie ; Smith, Kiki ; Smithson, Robert ; Stadtbäumer, Pia ; Steinbach, Haim ; Taaffe, Philip ; Takis ; Tillmans, Wolfgang ; Trockel, Rosemarie ; Vaisman, Meyer ; Vercruysse, Jan ; Wallace & Donohue ; Ward, Nari ; Warhol, Andy ; Wool, Christopher
Engels
Everything that's interesting is ...new : The Dakis Joannou Collection, Athens School of Fine Arts, "the factory", Athens, Museum of Modern Art, Copenhagen, Guggenheim Museum Soho, New York, 04-1996
boek